2004
DOI: 10.1111/j.1600-0501.2004.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between interleukin‐1 gene cluster polymorphisms and early implant failure in non‐smoking patients

Abstract: This study suggests that polymorphisms in the interleukin-1 gene cluster are not associated with early implant failure in a non-smoking Brazilian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 50 publications
6
53
2
Order By: Relevance
“…Regarding ethnic status, Caucasians were prevalent compared with Afro-Americans/mulatto individuals; however, no further analysis was performed based on such classification in view of the high genetic miscegenation of the Brazilian population (40). The frequencies of IL-1␤(3954) genotypes and alleles were found to be similar in the CP and C groups (Table 3) and were also found to be similar to those reported for the Brazilian population in previous studies (4,34,56).…”
Section: Il-1␤(3954c/t) Snp Frequency Analysis In C and Cp Groupssupporting
confidence: 64%
“…Regarding ethnic status, Caucasians were prevalent compared with Afro-Americans/mulatto individuals; however, no further analysis was performed based on such classification in view of the high genetic miscegenation of the Brazilian population (40). The frequencies of IL-1␤(3954) genotypes and alleles were found to be similar in the CP and C groups (Table 3) and were also found to be similar to those reported for the Brazilian population in previous studies (4,34,56).…”
Section: Il-1␤(3954c/t) Snp Frequency Analysis In C and Cp Groupssupporting
confidence: 64%
“…(Table 1) or between survivors and nonsurvivors. Allele frequencies of all polymorphisms within the control group were similar to previously published results (9,11,12 ).…”
supporting
confidence: 76%
“…Nevertheless, no significant associations between the distributio of the IL-1A and IL-1B genotypes and periodontal status were found. In contrast to these findings, most of the studies showed an elevated frequency of heterozygous (1.2) and a markedly decreased prevalence of homozygous (2.2) for both IL-1 genes [5,7,15,18,20]. Using a regression model, only age (P ¼ 0.015), bleeding on probing (P < 0.001) and HIV infection (P ¼ 0.005) had an effect on the outcome of chronic periodontitis.…”
mentioning
confidence: 77%